Ownership structure, family control, and acquisition decisions - Caprio, Lorenzo; Croci, Ettore; Del Giudice, Alfonso (Journal of Corporate Finance, 2011)
We investigate how ownership and family control influence the decision to take part in M&As as an acquirer or as an acquired company in a sample of 777 large Continental European companies in the period 1998–2008. We find that ownership is negatively correlated with the probability of launching a takeover bid, and family firms are less likely to make acquisitions, especially when the stake held by the family is not large enough to assure the persistence of family control. On the passive side of M&A deals, the effect of the largest shareholders' ownership on the decision to accept an acquisition proposal depends non-linearly on the voting rights they hold, and family control reduces the probability of being acquired by an unrelated party. We do not find evidence that family-controlled firms destroy wealth when they acquire other companies. Finally, we document that ownership and family control, while being negatively correlated with M&A activity, are not negatively correlated with growth in firm size.